Plant growth and nitrate absorption and assimilation of two sweet potato cultivars with different N tolerances in response to nitrate supply - Duan, Wenxue; Wang, Shasha; Zhang, Haiyan; Xie, Beitao; Zhang, Liming (Scientific reports, 2024)
In sweet potato, rational nitrogen (N) assimilation and distribution are conducive to inhibiting vine overgrowth. Nitrate (NO 3 - ) is the main N form absorbed by roots, and cultivar is an important factor affecting N utilization. Herein, a hydroponic experiment was conducted that included four NO 3 - concentrations of 0 (N0), 4 (N1), 8 (N2) and 16 (N3) mmol L -1 with two cultivars of Jishu26 (J26, N-sensitive) and Xushu32 (X32, N-tolerant). For J26, with increasing NO 3 - concentrations, the root length and root surface area significantly decreased. However, no significant differences were observed in these parameters for X32. Higher NO 3 - concentrations upregulated the expression levels of the genes that encode nitrate reductase ( NR2 ), nitrite reductase ( NiR2 ) and nitrate transporter ( NRT1.1 ) in roots for both cultivars. The trends in the activities of NR and NiR were subject to regulation of NR2 and NiR2 transcription, respectively. For both cultivars, N2 increased the N accumulated in leaves, growth points and roots. For J26, N3 further increased the N accumulation in these organs. Under higher NO 3 - nutrition, compared with X32, J26 exhibited higher expression levels of the NiR2 , NR2 and NRT1.1 genes, a higher influx NO 3 - rate in roots, and higher activities of NR and NiR in leaves and roots. Conclusively, the regulated effects of NO 3 - supplies on root growth and NO 3 - utilization were more significant for J26. Under high NO 3 - conditions, J26 exhibited higher capacities of NO 3 - absorption and distributed more N in leaves and in growth points, which may contribute to higher growth potential in shoots and more easily cause vine overgrowth.